Interval of Routine Maintenance and Maintenance Performance: A Literature Review - Au-Yong, Cheong Peng; Ali, Azlan Shah; Chua, Shirley Jin Lin (2016)
In high-rise residential buildings, the quality of facilities management services is significant to the normal operation of the facilities. Unfortunately, lack of concern towards building maintenance, especially preventive maintenance, happens in domestic housing industry in Malaysia. Majority of the maintenance operations of condominiums suffer from lack of planning, lack of proactive maintenance plan, and lack of proper implementation. Thus, this paper reviews the implementation of preventive maintenance strategy, routine maintenance in specific. An extensive review of literature published in 1987 to 2014 is performed for the purpose of this research. The publications are sourced from journal articles, conference proceedings and books. The literature analysis confirms that the routine maintenance of facilities and building services is vital and it can be influential towards the maintenance performance. Subsequently, a theoretical framework is developed, which shows the relationship between routine maintenance of building facilities & services and maintenance performance. The building facilities & services are divided into two categories. They are essential facilities & services that ensure the safety, health, habitability, and operability of buildings; while value-added facilities & services deal with property value, return on investment, and quality living of buildings. Based on the findings, a future research is proposed, which aims to identify the appropriate routine of maintenance for the facilities and services in high-rise residential buildings to improve the maintenance performance.